2023
DOI: 10.3390/genes14050968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Verification of a microRNA Panel Using Quadratic Discriminant Analysis for the Classification of Human Body Fluids in DNA Extracts

Abstract: There is significant interest in the use of miRNA analysis for forensic body fluid identification. Demonstrated co-extraction and detection in DNA extracts could make the use of miRNAs a more streamlined molecular body fluid identification method than other RNA-based methods. We previously reported a reverse transcription-quantitative PCR (RT-qPCR) panel of eight miRNAs that classified venous and menstrual blood, feces, urine, saliva, semen, and vaginal secretions using a quadratic discriminant analysis (QDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Therefore, it is proposed in this study to expand the previously reported microbial 16S triplex to incorporate a miRNA reverse transcription‐qPCR (RT‐qPCR) duplex that can now differentiate between vaginal/menstrual secretions, feces, saliva, blood, and semen at the quantification step of the forensic DNA workflow [17]. Our previous work on body fluid classification using miRNAs had previously identified and validated miR‐891a and let‐7g as being useful as markers for distinguishing blood and semen, and as an internal control, respectively [46].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is proposed in this study to expand the previously reported microbial 16S triplex to incorporate a miRNA reverse transcription‐qPCR (RT‐qPCR) duplex that can now differentiate between vaginal/menstrual secretions, feces, saliva, blood, and semen at the quantification step of the forensic DNA workflow [17]. Our previous work on body fluid classification using miRNAs had previously identified and validated miR‐891a and let‐7g as being useful as markers for distinguishing blood and semen, and as an internal control, respectively [46].…”
Section: Introductionmentioning
confidence: 99%